A generic streaming data acquisition system for high-energy physics experiments. (1st March 2022) - Wang, T.; Yang, J.; Sun, Z.; Zhang, L.; Song, K.
Abstract: The data acquisition system is a vital component in the high-energy physics experiment. To reduce redundant developments and allow for a fast setup under changing conditions, D-Matrix has been developed as an integrative solution in digital signal domain, including the hardware infrastructure and the data handling logical system. Its philosophy is to abstract different tasks in the data processing and encapsulate them as reusable modules with standard inter-module connectors. Furthermore, D-Matrix builds a unified model to integrate software and hardware design so that the system can be built from a global view. D-Matrix will be used in ion cooler-storage-ring external-target experiments. It aims at the research of phase structure of cold and high baryon density nuclear matter and the equation of states of cold asymmetric nuclear matter at supra-saturation densities. This DAQ can also be used in other high-energy physics experiments with little modifications. This paper presents the architecture and some details of the D-Matrix.